Low Temperature NO Storage of Zeolite Supported Pd for Low Temperature Diesel Engine Emission Control - Chen, Hai-Ying; Collier, Jillian E.; Liu, Dongxia; Mantarosie, Loredana; Durán-Martín, Desirée; Novák, Vladimír; Rajaram, Raj R.; Thompsett, David (Catalysis letters, 2016)
Pd supported on various zeolites has been found to be able to adsorb NO at temperatures below 200 °C with high storage efficiency and capacities in a gas feed which simulate diesel engine exhaust conditions. Highly dispersed Pd at the exchange sites of the zeolites are believed to be the active site for the low temperature NO storage. Different framework structures of the zeolites significantly affect not only the NO storage capacity but also the NOx desorption temperature. These materials show high potential for low temperature NOx emission control. Graphical Abstract